1986
DOI: 10.1002/ajp.1350100207
|View full text |Cite
|
Sign up to set email alerts
|

Social behavior and genital swelling in pregnant chimpanzees (Pan troglodytes)

Abstract: Previous reports of increased sexual activity associated with genital swelling during chimpanzee pregnancy have suggested that the tumescent pregnant female may be regarded as a regularly cycling estrous female. Analysis of additional data from seven pregnant and eight cycling females, however, indicated that tumescent pregnant females differed from cycling females in some social interactions with males. As in earlier reports, pregnant females were more receptive to male-initiated copulatory bouts. In addition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

1992
1992
2011
2011

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 31 publications
3
28
0
Order By: Relevance
“…Genital swelling data were analyzed using three categories: no swelling, partial swelling, and full swelling. A full swelling was defined as maximal swelling of the labia minora and perianal tissues resulting in labial occlusion, a deeply recessed anus and a shiny taut appearance [following Wallis and Lemmon, 1986;Dahl et al, 1991]. Three facility employees were responsible for the daily recording of genital swelling data; however, one person recorded 75% of these data.…”
Section: Genital Swelling Recordsmentioning
confidence: 99%
“…Genital swelling data were analyzed using three categories: no swelling, partial swelling, and full swelling. A full swelling was defined as maximal swelling of the labia minora and perianal tissues resulting in labial occlusion, a deeply recessed anus and a shiny taut appearance [following Wallis and Lemmon, 1986;Dahl et al, 1991]. Three facility employees were responsible for the daily recording of genital swelling data; however, one person recorded 75% of these data.…”
Section: Genital Swelling Recordsmentioning
confidence: 99%
“…The opposite trend has been reported for swellings in pregnant chimpanzees. In chimpanzees, swellings are confined to the first third of the gestation period, and full swellings overall are rare (8.7% in captivity [Wallis & Lemmon, 1986] and 9.4% in the wild [Wallis & Goodall, 1993]), while they are rather common in pregnant silvered langurs (27.5% overall). It seems that swellings (particularly full swellings) to some degree ''advertise'' gestation.…”
Section: Swellings In Pregnant Femalesmentioning
confidence: 96%
“…We assume here that female dispersal occurs regularly in silvered langurs, because it has been documented in other species of the genus (see summary in Sterck [1998]). Originally, it was argued that swellings in general [Tenaza, 1989] and during the gestation period in particular [Wallis & Lemmon, 1986] may facilitate dispersal as long as a female with a swelling can be mistaken for a cycling female. However, this seems unlikely in silvered langurs, and the question for now must remain unanswered.…”
Section: Swellings In Pregnant Femalesmentioning
confidence: 99%
“…He noted that cycling females with conspicuous ano-genital swellings tended to receive meat from adult males more frequently than did females without these sexual swellings, and suggested that males shared meat with females in exchange for sexual access. Swollen females are attractive to males (Dixson 1998) as the swellings generally indicate approaching ovulation, although females will also show swellings when pregnant (Wallis and Lemmon 1986). Supporting evidence for this hypotheses was provided by Stanford (1998) who found that, at Gombe, the presence of a swollen female in a party of chimpanzees was the best predictor of a hunt occurring when encountering a group of red colobus, and reported five observations of females begging for meat from males, and only being given part of the kill after copulating.…”
Section: Hunting For Trade Goodsmentioning
confidence: 99%